Design and Analysis of Biomedical Scaffolds Using TPMS‐Based Porous Structures Inspired from Additive Manufacturing - Verma, Rati; Kumar, Jitendra; Singh, Nishant Kumar; Rai, Sanjay Kumar; Saxena, Kuldeep K.; Xu, Jinyang (MDPI, 2022)
Gyroid (G) and primitive (P) porous structures have multiple application areas, ranging from thermal to mechanical, and fall in the complex triply periodic minimal surface (TPMS) category. Such intricate bioinspired constructs are gaining attention because they meet both biological and mechanical requirements for osseous reconstruction. The study aimed to develop G and P structures with varying porosity levels from 40% to 80% by modulating the strut thickness to proportionally resemble the stiffness of host tissue. The performance characteristics were evaluated using Ti6Al4V and important relationships between feature dimension, strut thickness, porosity, and stiffness were established. Numerical results showed that the studied porous structures could decrease stiffness from 107 GPa (stiffness of Ti6Al4V) to the range between 4.21 GPa to 29.63 GPa of varying porosities, which matches the human bone stiffness range. Furthermore, using this foundation, a subject‐specific scaffold (made of P unit cells with an 80% porosity) was developed to reconstruct segmental bone defect (SBD) of the human femur, demonstrating a significant decrease in the stress shielding effect. Stress transfer on the bone surrounded by a P scaffold was compared with a solid implant which showed a net increase of stress transfer of 76% with the use of P scaffold. In the conclusion, future concerns and recommendations are suggested.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: CAD design; finite element method; implant; lattice structures; mechanical; patient‐specific; porous; scaffold